2014
DOI: 10.1021/am505305g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Strongly Fluorescent Molybdenum Disulfide Nanosheets for Cell-Targeted Labeling

Abstract: MoS2 nanosheets with polydispersity of the lateral dimensions from natural mineral molybdenite have been prepared in the emulsions microenvironment built by the water/surfactant/CO2 system. The size, thickness, and atomic structure are characterized by transmission electron microscopy (TEM), atomic force microscopy (AFM), and laser-scattering particle size analysis. Meanwhile, by the analysis of photoluminescence spectroscopy and microscope, the MoS2 nanosheets with smaller lateral dimensions exhibit extraordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 58 publications
4
65
1
1
Order By: Relevance
“…14,[30][31][32] The PL properties of the prepared MoS 2 QDs investigated at different excitation wavelengths are presented in Fig. 4.…”
Section: Tunable Photoluminescence Of Mos 2 Qdsmentioning
confidence: 99%
See 2 more Smart Citations
“…14,[30][31][32] The PL properties of the prepared MoS 2 QDs investigated at different excitation wavelengths are presented in Fig. 4.…”
Section: Tunable Photoluminescence Of Mos 2 Qdsmentioning
confidence: 99%
“…33 As reported in the literature, the luminescence properties of MoS 2 QDs depend on their particle size, which is similar as the quantum size effect of semiconductor QDs. 14,15 This means that the aim to control the PL of MoS 2 QDs could be realized by adjusting their size. In colloidal solution, some experiment conditions, including reaction temperature and time, the amount of ligands, would influence the size of nanomaterials.…”
Section: Tunable Photoluminescence Of Mos 2 Qdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent results have demonstrated that certain members of TMDCs were featured with low cytotoxicity, high hemo/histocompatibility and high photothermal-conversion efficiency [75][76][77][78][79][80][81]. Especially, their high biocompatibility and biosafety guarantee their potential applications in biological-and biomedicine-related fields [82][83][84][85][86][87][88][89][90][91][92][93]. In Representative scheme of in vivo PTT tumor ablation assisted by 2D nanosheets and the balance between the biosafety and PTT efficiency.…”
Section: Transition Metal Dichalcogenidesmentioning
confidence: 99%
“…MoS 2 , a two-dimensionally layered transition metal dichalcogenides, has been widely employed in material science because of its excellent physicochemical properties, with applications in opto-electronics, 19 catalysis, 20 energy storage, 21 biosensing, 22 fluorescence imaging 23 and photothermal therapeutic applications. 24 The photothermal conversion properties of MoS 2 directly correspond to one of the requirements of a matrix for the LDI-MS analysis of small molecules.…”
Section: Introductionmentioning
confidence: 99%